Effectiveness of Mixed Strain Probiotics on the Performance of Broiler Chickens Reared in an Open Cage System - Rabbani, Azhar; Cahyanto, Ardian Dwi; Tugiyanti, Elly; Rosidi, Rosidi; Suswoyo, Imam (JURNAL ILMIAH PETERNAKAN TERPADU, 2025)
This research aims to assese the effect of probiotics as feed additives in broiler chicken feed kept in open housed on the feed consumption, weight gain, feed conversion ratio and percentage of broiler chicken carcasses. The study involved 100 male Cobb strain broiler chickens kept from day old chick until they were culled at 35 days of age. The research design implemented was a completely randomized design featuring 4 treatments and 5 replications, resulting in 20 experimental units. Every experimental unit was made up of 5 broiler chickens. The intervention applied involved adding probiotics, which included P0: Commercial feed (control), P1: Commercial feed + 0.2% Bacillus coagulans Probiotic, P2: Commercial feed + 0.2% Saccharomyces cerevisiae Probiotic, P3: Commercial feed + Mied-strain probiotic comprising both Bacillus coagulans and Saccharomyces cerevisiae at 0.1% each. The variables measured  consist of feed intake, weight gain (WG) ,feed conversion ratio(FCR) and carcass percentage. Data analysis using analysis of variance. The value of feed consumption values is 640.37±136.89 to 661.92±142.68 grams/head/week with an average of 654.32±142.99 grams/head/week. The range of body weight gain values is 491.03±234.46 to 518.8±236.41 grams/head/week with an average of 502.35±247.72 grams/head/week. The FCR values ​​range from 1,47±0,05 to 1,95±0,15 with an average of 1,75±0,18. The range of carcass percentage results is 62.17% to 68.79% with an average of 65.20%±1.76%. The analysis of variance indicate that incorporating probiotics as a feed additive does not significantly impact (P>0.05) feed intake, weight gain, FCR rate, or carcass yield. The inclusion of probiotics Bacillus coagulans and Saccharomyces cerevisiae at 0.2% and mixed strains in feed has failed to enhance feed intake, body weight, feed conversion ratio, and carcass percentage of broiler chickens raised in open housed. The provision of probiotics Bacillus coagulans, Saccharomyces cerevisiae as much as 0.2% and mix strain in feed has not been able to improve feed consumption, first of all body weight, FCR and percentage of carcass of broiler chickens raised in open cages.